Economization Discourse in the Process of Creating Professional Ideas of Family Assistants - Izabela Kamińska-Jatczak (Social Work & Society, 2017)
This article characterizes the construction of the educational discourse, referred to as the economization discourse, which is used to educate family assistants, case workers (Polish social workers). The author presents the thesis that the economization discourse transfers the ideology of economization into the area of assistants' training. This ideology, based on the paradigm of thinking consistent with homo oeconomicus, may influence the process of creating perceptions of professional assistants on the essence of the activities undertaken in their work.